Integrated tourism policy: The Buffer area development impact of Borobudur world heritage - Dwi Harsono; Ibnu Wijayanto (Informasi, 2022)
This article addresses the development policy practice by the Borobudur Authority Agency. The policy can synchronize different autonomous local government policies and avoid conflictual approaches to its neighborhoods. Even though a top-down policy may reduce the creativity of local governments to develop their tourism programs, this research shows the impact of the integrated tourism policy of the Borobudur National Tourism Strategic Area benefited accelerating tourism development. The economic impact on the surrounding community is creating job opportunities and increasing people’s financial revenue. The effects on the social dimension show that tourism development activities under borderless policy sites increase interaction and bonds among communities and preserve the cultures and folklores within the research sites that are administratively separated regions. When viewed from the environmental aspect, tourism development activities have implemented a sustainable approach by applying nomadic tourism concepts and building construction that does not damage the soil structure. By informing those impacts, this paper suggests newsworthiness as a guiding principle to communicate the successful implementation of a public policy.